Editor's choice: Infections, sexual reproductive health and non-communicable diseases. - Tumwine, James K. (African Health Sciences, 2024)
We bring you this December 2024 Issue of African Health Sciences in a season when the Africa region is grappling with infectious diseases such as Mpox. Fortunately, the Marburg outbreak in the region has been nipped in the bud, and there is a semblance of relief in East Africa. In this issue, we bring you articles in 4 main categories: Infectious diseases; sexual and reproductive health; Non-communicable Diseases; Child Health, and other issues